Spazio urbano e homo oeconomicus. Caro-affitti e produzione dell'uomo indebitato - Fagioli, Andrea (2017)
This paper focuses on the relationships between urban space and the production of neoliberal subject. Rather than proposing an all-encompassing perspective of both concepts, the paper analyses the relationships between rent and the making of the subjective figure of the ‘indebted man’, as has been outlined by Maurizio Lazzarato. The work consists of two parts and aims to shed light on the double function of capitalist city: a space of reproduction and valorisation of capital, and a means of neutralization of revolutionary ruptures. In the first part, we will analyse the function of cities in modern capitalist era as has been explored by Henri Lefebvre, in order to outline the central role played by cities during the industrial capitalist stage (a space organized by capital and, at the same time, a space of reproduction of capital). Then, we hypothesize that urban space plays a crucial role in the valorisation of capital during its extractive stage. In the second part, we will suggest that cities are essential instruments in producing the subjective figure of the ‘indebted man’. More specifically, we will focus on the function of rent in cities as means of colonisation of future, limiting the undetermined forms of human life to the only ones that are actually capable of refunding the ‘debt’.